Echocardiography of coarctation of the aorta, aortic arch hypoplasia, and arch interruption: strategies for evaluation of the aortic arch. (2nd February 2017) - Goudar, Suma P.; Shah, Sanket S.; Shirali, Girish S.
Abstract : Aim: Echocardiography is the modality of choice for the diagnosis and serial follow-up of aortic arch pathology. In this article, we review the types of obstruction of the aortic arch, various classification schemes of coarctation of the aorta and interrupted aortic arch, methodology for optimal echocardiographic imaging of the aortic arch, and key echocardiographic measurements for accurate diagnosis of obstruction and hypoplasia of the aortic arch. Finally, we will discuss the limitations of echocardiography in optimal imaging of the aortic arch and the use of other non-invasive imaging modalities such as CT or MRI to provide additional information in these cases. Background: Coarctation of the aorta is the more common lesion of the two, with an estimated incidence of four in every 10, 000 live births in the United States of America. Interrupted aortic arch is rarer, with an incidence of 19 per one million live births. 1 There is a spectrum of pathology of obstruction of the aortic arch, ranging from coarctation of the aorta with and without hypoplasia of the arch to interrupted aortic arch. Both these lesions are frequently encountered in congenital cardiology practice, and will be discussed in the remainder of this article. Obstruction of the aortic arch in the setting of hypoplastic left heart structures or atresia of the aortic valve is beyond the scope of this review and will not be discussed further.